Genotyping of Klebsiella spp. isolated from different clinical sources - Al- Rubaye, Dalal S.; Hamza, Heba Mohammed; Abdulrahman, Thanaa R. (Iraqi Journal of Science, 2022)
A total of 172 clinical were obtained over 6 months. Klebsiella spp. was detected in 58 (33.7%) samples with a high percentage 29 (50%) in urine in female and low percentage 1(1.7%) in pus and burn swabs in male, and the vaginal swab was 1(1.7%). The female to male ratio was 3.1:1. PCR detection showed that 51(87.93%) out of 58 produce 108 bp. product with rpoB specific primer that represented K. pneumonia. Whereas 7(12.07%) showed PCR product with 343 bp by K. oxytoca specific primer (peh X), furthermore, the sequences of two selected isolates showed that the species related to K. oxytoca strain CAV1335, and to K. oxytoca strain CAV1374. Five selected isolates were re-tested by the gyr A primer, all were showed specific band product with 441bp. Sequencing blast analysis for these isolates showed that one was related to K. pneumoniae subsp. pneumoniae strain RJF999, two isolates related to K. pneumoniae strain 17265 GyrA, one related to K. oxytoca strain 7102 GyrA and one related to K. pneumonia isolate 103 GyrA gene. Phylogenetic tree analysis showed the relation of 3 K. pneumoniae isolates to USA and UK strains and one with the Asian strains, and 2 K. oxytoca isolates have a relation within the Iranian strains and one has a genetic variation.